Estimating the Impact of Reducing Violence Against Female Sex Workers on HIV Epidemics in Kenya and Ukraine: A Policy Modeling Exercise. (6th February 2013) - Decker, Michele R.; Wirtz, Andrea L.; Pretorius, Carel; Sherman, Susan G.; Sweat, Michael D.; Baral, Stefan D.; Beyrer, Chris; Kerrigan, Deanna L.
Abstract : Problem: Female sex workers (FSWs) worldwide suffer disproportionate burdens of HIV and gender‐based violence. Despite evidence linking these threats, little is known about the potential HIV epidemic impact of reducing abuse. Method of study: The Goals model approximated the impact of reducing violence against FSWs on HIV epidemics in Ukraine and Kenya, measured by reductions in new infections among FSWs and adults. Cumulative infections averted over a 5‐year period, in which violence declined was calculated, relative to a status quo with no reduction. Projections held HIV interventions constant at baseline levels; subsequently, scenarios adjusted for planned expansion of antiretroviral therapy (ART) coverage. Results: An approximate 25% reduction in incident HIV infections among FSWs was observed when physical or sexual violence was reduced; cumulative infections averted were 21, 200 and 4700 in Kenya and Ukraine, respectively. Similar percent reductions were observed assuming ART coverage expansion, with approximately 18, 200 and 4400 infections averted among FSWs in Kenya and Ukraine. New infections were also averted in the general population. Conclusion: Reducing violence against FSWs appears to impart significant reductions in new infections among FSWs and in the general adult population in both generalized and concentrated epidemics. Limitations provide direction to improve the precision of future estimates.